The Effect of Training and Career Development on Employee Performance at PT Sumber Anugrah Prima - Apuy, Marten; Suarni, Suarni; Hayati, Sri; Orianto, Agustina Lisa (CV. Publikasi Indonesia, 2024)
One strategy to enhance employee performance is through the implementation of training and development programs. The objective of this study is to evaluate the impact of “training and development of human resources” on employee performance at PT Sumber Anugrah Prima located in Samarinda. The methodology used in this research is associative with a quantitative approach. The research was conducted within PT Sumber Anugrah Prima and used saturated sampling technique, where 63 employees were used as respondents. The results of the analysis show that both individually and simultaneously, the variables of training and career development have a significant effect on employee performance at PT Sumber Anugrah Prima Samarinda. The R Square value obtained is 0.701, or 70.1%, indicating that training and career development make a substantial contribution to improving employee performance.